Monitoring of the dynamics of antimicrobial resistance among wounded in the conditions of armed conflict - L. K. Sorokoumova; A. A. Kozhokaru; S. Yu. Yaremin; О. І. Zhorniak (Український журнал військової медицини, 2025)
Introduction. The article presents the results of monitoring antibiotic resistance of microorganisms isolated from military personnel undergoing long-term treatment in specialized hospitals. A high level of resistance to antibacterial drugs was established. The predominance of gram-negative microflora was noted not only in the general structure of the development of purulent-inflammatory processes, but also in resistance. Of particular concern are isolates that have proven to be resistant to the reserve group of drugs.